Social history of the Jews in antiquity: studies in dialogue with Albert Baumgarten - Bar Asher Sigal, Mikhal; Ben-Dov, Yonatan (Texts and studies in ancient Judaism, 2021)
Cover -- Title -- Table of Contents -- Michal Bar-Asher Siegal, Jonathan Ben-Dov, and Eyal Regev - Albert Baumgarten: Contextualizing the Ancient Jewish Experience -- I. Second Temple Studies -- Gabriele Boccaccini - Jewish Scholarship on the Second Temple Period from the Renaissance to Albert I. Baumgarten -- Martin Goodman - Philo's Extreme Allegorists Revisited -- Maxine L. Grossman - The Dead Sea Sectarians. Breaking the Boundaries of an Essene-Shaped Space -- Charlotte Hempel - Self-Fashioning in the Dead Sea Scrolls. Thickening the Description of What Rule Texts Do -- Sylvie Honigman - Social and Economic Upheavals and the "De-Traditionalization" of Judean Society in Hellenistic Times. The Background to Sectarianism -- Steve Mason - John of Gischala and Simon bar Giora from Gerasa. A National Revolt? -- Eyal Regev - The Practice of Piety. The Puritans and Qumran -- Daniel R. Schwartz - Who Brought on Antiochus's Decrees? On the Chaotic and "Worthless" Prehistory of Bickerman's Gott der Makkabäer -- Daniel Stökl Ben Ezra - The Place of 4QMMT in the Corpus of Qumran Manuscripts. Beyond the Sussmann-Schiffman Dichotomy -- II. Rabbinics and Early Christianity -- Michal Bar-Asher Siegal - Public Confession in the Babylonian Talmud and in Contemporary Christian Sources -- Jonathan Ben-Dov - Rabbi Yehuda Hanasi and the Roman Year -- Shaye J. D. Cohen - Are Women and Gentiles "Persons" (Adam, Benei Adam) in the Eyes of the Mishnah? -- Steven D. Fraade - "Reading Leads to Translating" in a Multilingual Context. The View from Early Rabbinic Texts (and Beyond) -- Maren R. Niehoff - Celsus's Jew in Third-Century Caesarea. Tracing Hellenistic Judaism in Origen's Contra Celsum -- Adele Reinhartz - The Fourth Gospel and the First Century Outreach Campaign to the Gentiles -- Adiel Schremer - How Can Rabbinic Narratives Talk History?.